Tout est au mieux dans ce meilleur des ménages possibles The Pangloss critique of equivalence scales - Jo Thori Lind (Statistics Norway, Research Department, 2001)
A common approach to defining equivalence scales is to consider a household modelled as if it maximizes a single utility function. This may be founded on an assumption of the household maximizing a welfare function of individual utilities. For a positive analysis of the household, this may be appropriate, but it is argued that basing inter-household comparisons of welfare on this approach is generally not valid. The household will generally put different weight on the utility of the various household members, and this weighting does not necessarily correspond to society's aggregation of utility. This complication is called the Pangloss problem. An alternative definition of equivalence scales taking this into account is introduced and discussed.
Keywords: D11; D12; D31; D63; 330; Equivalence scales; household; welfare function; Pangloss problem; intra-household distribution; children